Study of a New Composite Material Rt800 Reinforced with Polyte 440-M888 in Endurance Conditions. (2016) - Modrea, Arina; Gheorghe, Vasile; Sandu, Venetia; Teodorescu-Draghicescu, Horatiu; Mihalcica, Mircea; Scutaru, Maria Luminita
Abstract: This paper aim to determine the analytical form of the Wöhler function F which is associated with the behavior of the composite material made of polyester resin reinforced with 5 layers of glass fiber fabric, RT800, with the specific mass of 845 g /m 2, reinforced with Polyte 440-M888.